More Than Just Skills: How Competencies, Motivations, and Social Capital Shape New Venture Performance - Rizky, M. Chaerul; Faried, Annisa Ilmi; Purba, Echa Ferina Br. (International Review of Management and Marketing, 2025)
Entrepreneurial success is shaped by the interplay of individual competencies, intrinsic and extrinsic motivations, and access to social capital. While prior studies have explored these factors independently, their combined impact on new venture performance remains underexamined. Grounded in the Resource-Based View (RBV) and Social Capital Theory, this study investigates the role of entrepreneurial competencies, motivations, and social capital in shaping business success. Using data from 360 owner-managers of small and medium enterprises (SMEs) in North Sumatera, Indonesia, this study applies Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine the proposed relationships. The findings reveal that both competencies and motivations significantly influence venture performance, while social capital moderates these relationships. Notably, social capital strengthens the effect of competencies but weakens the direct influence of motivations on business outcomes. These results highlight the complex role of social capital, which can serve as both an enabler and a constraint depending on the entrepreneurial context. This study contributes to the theoretical discourse by integrating human and social capital perspectives, while offering actionable insights for policymakers and practitioners seeking to foster entrepreneurial growth. Future research should explore the contextual nuances of these relationships across different industries and economic landscapes.